Telomere length and genetic variant associations with interstitial lung disease progression and survival. Issue 4 (11th April 2019) - Newton, Chad A.; Oldham, Justin M.; Ley, Brett; Anand, Vikram; Adegunsoye, Ayodeji; Liu, Gabrielle; Batra, Kiran; Torrealba, Jose; Kozlitina, Julia; Glazer, Craig; Strek, Mary E.; Wolters, Paul J.; et al.
Leukocyte telomere length (LTL), MUC5B rs35705950 and TOLLIP rs5743890 have been associated with idiopathic pulmonary fibrosis (IPF). In this observational cohort study, we assessed the associations between these genomic markers and outcomes of survival and rate of disease progression in patients with interstitial pneumonia with autoimmune features (IPAF, n=250) and connective tissue disease-associated interstitial lung disease (CTD-ILD, n=248). IPF (n=499) was used as a comparator. The LTL of IPAF and CTD-ILD patients (mean age-adjusted log-transformed T/S of −0.05±0.29 and −0.04±0.25, respectively) is longer than that of IPF patients (−0.17±0.32). For IPAF patients, LTL <10th percentile is associated with faster lung function decline compared to LTL ≥10th percentile (−6.43% per year versus −0.86% per year; p<0.0001) and worse transplant-free survival (hazard ratio 2.97, 95% CI 1.70–5.20; p=0.00014). The MUC5B rs35705950 minor allele frequency (MAF) is greater for IPAF patients (23.2, 95% CI 18.8–28.2; p<0.0001) than controls and is associated with worse transplant-free IPAF survival (hazard ratio 1.92, 95% CI 1.18–3.13; p=0.0091). Rheumatoid arthritis (RA)-associated ILD (RA-ILD) has a shorter LTL than non-RA CTD-ILD (−0.14±0.27 versus −0.01±0.23; p=0.00055) and higher MUC5B MAF (34.6, 95% CI 24.4–46.3 versus 14.1, 95% CI 9.8–20.0; p=0.00025). Neither LTL nor MUC5B are associated with transplant-free CTD-ILD survival. LTL and MUC5B MAF have different associations with lung function progression and survival for IPAF and CTD-ILD. Leukocyte telomere length and MUC5B minor allele frequency are similar for IPAF and the combined CTD-ILD group; however, the associations between these genomic markers and clinical outcomes are different for these two types of ILD http://ow.ly/wXem30njRkg